1990
DOI: 10.1002/rcm.1290041024
|View full text |Cite
|
Sign up to set email alerts
|

The use of tandem mass spectrometry for the differentiation of bile acid isomers and for the identification of bile acids in biological extracts

Abstract: Tandem mass spectrometric (MS/MS) techniques have been widely used for the differentiation of isomeric compounds, since their spectra may show differences sufficient to distinguish between them. There are several different ways by which the MS/MS data can be obtained depending on the energies of the ions and the collisions. In this paper MS/MS spectra have been obtained for a group of isomeric bile acids using: 1, low-energy ions and low-energy collisions in a triple quadrupole mass spectrometer by liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, up to now there are no LC-MS/MS methods published with a sufficient separation of isobaric BA species below 10 min runtime [5,6,8,9,11,14,[16][17][18][19]. Therefore, we developed a LC-MS/MS method for simultaneous determination of free and conjugated BAs in plasma and serum with a runtime of 6.5 min.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, up to now there are no LC-MS/MS methods published with a sufficient separation of isobaric BA species below 10 min runtime [5,6,8,9,11,14,[16][17][18][19]. Therefore, we developed a LC-MS/MS method for simultaneous determination of free and conjugated BAs in plasma and serum with a runtime of 6.5 min.…”
Section: Discussionmentioning
confidence: 97%
“…In the last years a number of methods using liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) were developed allowing analysis of free and conjugated BAs without derivatization [5][6][7][8][9][10][11][12][13][14][15][16]. Nevertheless, most methods show disadvantages with time consuming extraction procedures [5,8,17], long analysis times [6][7][8][14][15][16][17][18] or lack of baseline separation of isobaric species [5,8,9,17,18]. Direct BA analysis by ESI-MS/MS does not allow identification of isobaric species [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Libert et al (1991); Stroobant et al (1995); and Lemonde, Johnson, & Clayton (1999) have shown that informative CID spectra of bile acids can also be obtained at low collision‐energy (Table 2). Libert et al (1991) found that taurine‐conjugated Δ 4 ‐unsaturated bile acids give particularly informative low‐energy CID spectra; this result is in contrast to the spectra of glycine‐conjugated and unconjugated bile acids, which mostly show fragment ions generated by small neutral losses (Eckers et al, 1990, Eckers, East, & Haskins, 1991). The spectra of Δ 4 ‐unsaturated taurine conjugates gave a series of CRF fragment ions from which the position of unsaturation can readily be determined.…”
Section: Bile Acids and Conjugated Steroidsmentioning
confidence: 99%
“…Early methods based on fast atom bombardment [12] and thermospray ionization [12][13][14] have largely been replaced by softer techniques, such as electrospray ionization (ESI). HPLC in combination with ESI-MS/MS has been applied to the determination of glycine-and taurine-conjugated bile acids in plasma [15,16] as well as in other biological fluids, such as human gallbladder bile [17].…”
Section: Introductionmentioning
confidence: 99%